2018
DOI: 10.1080/01635581.2018.1524017
|View full text |Cite
|
Sign up to set email alerts
|

Diet and Behavior Modifications by Long-term Rectal Cancer Survivors to Manage Bowel Dysfunction-Associated Symptoms*

Abstract: Background: Rectal cancer (RC) survivors experience significant bowel function issues after treatment. We aimed to describe self-reported dietary and behavioral modifications among long-term (≥ 5 years) RC survivors to manage bowel dysfunction. Methods: RC survivors from Kaiser Permanente Northern California and Northwest regions completed surveys either via postage-paid return mail or telephone. Summary statistics on diet/behavioral modifications data were tabulated by proportion of responses. Modifications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Patients with advanced RC often have a worse prognosis than patients in the early stage due to the deterioration of their condition, tumor cells undergo metastasis and invasion, which seriously affect the physical health and life safety of patients [ 4 ]. Investigations have shown that RC is associated with diet, lifestyle, and genetic heritability in the population, but the specific pathogenesis remains unknown [ 5 , 6 ]. Therefore, it is beneficial for the prevention and treatment of rectal cancer to study the related factors affecting the occurrence and development of RC from the molecular level and find new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced RC often have a worse prognosis than patients in the early stage due to the deterioration of their condition, tumor cells undergo metastasis and invasion, which seriously affect the physical health and life safety of patients [ 4 ]. Investigations have shown that RC is associated with diet, lifestyle, and genetic heritability in the population, but the specific pathogenesis remains unknown [ 5 , 6 ]. Therefore, it is beneficial for the prevention and treatment of rectal cancer to study the related factors affecting the occurrence and development of RC from the molecular level and find new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Common late and long-term effects of treatment include oxaliplatin-induced peripheral neuropathy, bladder dysfunction, sexual dysfunction, and chronic diarrhea [ 19 , 20 ]. Bowel dysfunction is common among survivors of rectal cancer and is associated with frequent and erratic bowel movements, fecal incontinence, soiling, gas, bloating, and oscillations between diarrhea and constipation [ 21 , 22 ]. Persistent bowel symptoms lead to reduced social activities, poor emotional well-being, and decrements in QOL [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Current literature on V&F consumption among survivors with GI cancers report that although certain V&F might be helpful in managing specific GI complications, other V&F can exacerbate symptoms. For example, recent research of Sun and colleagues 56 on 575 survivors with long-term rectal cancer found that V&F were considered helpful for bowel symptoms, whereas their earlier work among 856 ostomy and anastomosis surgical patients found lower intakes of vegetables such as corn, onions, and lettuce. 57 Therefore, although overall differences in V&F intake may not exist among survivors of GI cancers compared with other cancers, intake of specific V&F may still differ.…”
Section: Discussionmentioning
confidence: 99%